Assessment of depression among elderly living in old age homes and within family set up in Bareilly city: A cross-sectional study - Nandita Gautam; Shivalingesh KK; Anushtha Kushwaha; Lubna Shoaib; Vertika Mahar (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2022)
Introduction: Aging is a natural process but at the same time, the aging population has substantially increased. Socially this stage is considered the total of one lived experience.  Materials and methods: The sample size has been 200 which is 100 in each group. Individuals beyond 60 years of age and who will be able to cooperate with the study were included in the study. Geriatric Depression Scale (GDS) was used to record depression among the same subject. The data were entered into an excel sheet and transferred to SPSS V. 21. for statistical analysis and Chi-square and ANOVA tests were done.  Results: The prevalence of depression in elderly individuals living in family settings was 22% mild, 14% moderate, and 10% severe, whereas, in old age homes, the prevalence was 36% mild, 26% moderate, and 8% severe. On comparison of depression according to marital status among the elderly within the family set up and old age home reported a statistically significant difference between the 2 groups (p < 0.001).  Conclusion: We found from this study that the overall prevalence of depression was higher in elderly people residing in old age homes. It is more common in older women than in men.